Sociolinguistic profile research paper - Turdimuradova Sitora O`ktamaliyevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper explores the sociolinguistic profile of a group of learners aged 15–16 preparing for the IELTS exam at an educational centre. The research analyses key learner variables such as language background, socioeconomic status, gender, and parental involvement, as well as the sociolinguistic context of their learning environment and the domain in which English will be used. Pedagogical and assessment implications are discussed to suggest tailored teaching strategies and tools that address the learners’ needs. The study highlights how understanding learners' sociolinguistic profiles can inform more equitable and effective language instruction.